2001
DOI: 10.1002/1097-0215(20010701)93:1<114::aid-ijc1309>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

DeterminingMDR1/P-glycoprotein expression in breast cancer

Abstract: The mechanism of chemotherapy resistance in breast cancer is unresolved. MDR1/P‐glycoprotein (P‐Gp) over‐expression confers multidrug resistance in vitro and might play a role in clinical breast cancer. Studies using clinical samples have yielded conflicting results. MDR1/P‐Gp mRNA expression was determined relative to the expression in normal human liver using TaqMan real‐time RT‐PCR (corrected for expression of the housekeeping gene PBGD). Immunohistochemistry (IHC) was performed with monoclonal antibodies a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(32 citation statements)
references
References 39 publications
0
30
0
Order By: Relevance
“…Immunohistochemical studies confirmed undetectable expression of BCRP in breast tumors, even in biopsies from women relapsing after doxorubicin-based chemotherapy (Faneyte et al, 2002).…”
Section: Expression Of Bcrp In Human Cancersmentioning
confidence: 76%
See 1 more Smart Citation
“…Immunohistochemical studies confirmed undetectable expression of BCRP in breast tumors, even in biopsies from women relapsing after doxorubicin-based chemotherapy (Faneyte et al, 2002).…”
Section: Expression Of Bcrp In Human Cancersmentioning
confidence: 76%
“…Normal tissues without detectable BCRP expression included endometrial cells and squamous epithelial cells in the skin or esophagus. BCRP is variably expressed by immunohistochemistry in normal breast epithelium and blood vessels (Faneyte et al, 2002). Low or undetectable BCRP expression in human and murine lung were also observed by immunohistochemical studies .…”
Section: Expression Of Bcrp In Normal Tissuesmentioning
confidence: 83%
“…Although BCRP was originally cloned from a human breast cancer cell line, its level of expression in clinical breast cancer samples was low, as measured using RT-PCR techniques [140], or undetectable when immunohistochemical techniques were applied [141]. However, in a large study encompassing 150 tumours from 21 different cancer types, BCRP expression was detected in over 40% of the tumours examined, with strong expression in gastric carcinoma, hepatocellular carcinoma, endometrial carcinoma, colon cancer, small cell lung cancer and melanoma [142].…”
Section: Bcrp Expression In Human Cancersmentioning
confidence: 99%
“…BCRP seems to be expressed at low levels in breast cancer cells as well as leukemic cells (Ross et al, 2000;Kanzaki et al, 2001). Furthermore, the expression of BCRP in breast carcinoma cells does not seem to correlate with response to doxorubicin-based chemotherapy (Kanzaki et al, 2001), nor is it upregulated in patients with breast cancer that were previously treated with anthracyclines versus those patients that were not treated with these drugs (Faneyte et al, 2002). Another recent study found that BCRP protein expression was increased in leukemia cells from three out of four patients following an infusion of topotecan and arabinoside-C .…”
Section: Cellular Accumulation and Transport Of Cptsmentioning
confidence: 99%